2014
DOI: 10.5901/ajis.2014.v3n6p327
|View full text |Cite
|
Sign up to set email alerts
|

Role of Emotional Intelligence on Job Satisfaction in University Teacher

Abstract: Emotional intelligence and job satisfaction are two concepts of high importance in the modern work environment. They serve as a competitive verge in personal and organizational life. The teaching profession is one the most important profession. A teacher can mold the future every day in the class. A teacher can make the world a better place, giving young people the best start in life and can use his own education to the fullest and best extent. The knowledge of Emotional Intelligence could help teachers to har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…The link between emotional intelligence and job satisfaction was determined by Mousavi et al (2012), of PET teachers, and a significant positive relationship between emotional intelligence and job satisfaction was found in the present study. Results are in line with Siddique et al (2014) whose study revealed a significant association between two variables emotional intelligence and job satisfaction in Pakistani Higher Education institutions.…”
Section: Wwwpsychologyandeducationnetsupporting
confidence: 89%
See 1 more Smart Citation
“…The link between emotional intelligence and job satisfaction was determined by Mousavi et al (2012), of PET teachers, and a significant positive relationship between emotional intelligence and job satisfaction was found in the present study. Results are in line with Siddique et al (2014) whose study revealed a significant association between two variables emotional intelligence and job satisfaction in Pakistani Higher Education institutions.…”
Section: Wwwpsychologyandeducationnetsupporting
confidence: 89%
“…Similarly, the results of the study revealed that there was a positive and significant correlation between two variables emotional intelligence and job satisfaction of EFL teachers in Iran/Shiraz (Hekmatzadeh, Khojasteh, & Shokrpour, 2016). Results of a study by Siddique et al (2014) demonstrated a significant association between two variables, emotional intelligence and job satisfaction of teachers of Pakistani higher education institutions.…”
Section: Introductionmentioning
confidence: 99%